Statin therapy for NAFLD: Molecular underpinnings of myopathic consequences and treatment strategies - Pratiksha Nanepag; Shubhada Mangrulkar; Aarti Shriwas; Mayur Kale; Sapana Kushwaha; Nitu Wankhede; Brijesh Taksande; Milind Umekar (Aspects of Molecular Medicine)
Non-alcoholic fatty liver disease (NAFLD) encompasses a range of hepatic disorders characterized by excessive lipid accumulation in hepatocytes and is closely linked to metabolic syndrome. Statins, which are potent lipid-lowering agents, have emerged as potential therapeutic options for managing NAFLD. Recent meta-analyses have demonstrated the efficacy of statins in reducing liver enzymes, improving histological features, and attenuating disease progression in patients with NAFLD. Mechanistically, statins exert their beneficial effects by inhibiting cholesterol synthesis, modulating lipid metabolism, and exhibiting anti-inflammatory and antifibrotic properties. They target key pathogenic pathways in NAFLD, including the inhibition of sterol regulatory element-binding proteins (SREBPs), activation of peroxisome proliferator-activated receptor-alpha (PPAR-α), and enhancement of fatty acid β-oxidation. Additionally, statins mitigate hepatic inflammation by reducing pro-inflammatory cytokines and oxidative stress, while promoting fibrosis regression through the inhibition of RhoA/Rho kinase signaling and transforming growth factor-beta (TGF-β) pathways. However, statin-associated muscle symptoms (SAMS) remain a significant concern, often leading to treatment non-adherence or discontinuation. The molecular mechanisms underlying statin-induced myopathy involve the inhibition of the mevalonate pathway, coenzyme Q10 depletion, mitochondrial dysfunction, and disruption of the ubiquitin-proteasome system. Strategies to prevent and manage SAMS include alternative dosing regimens, statin switching, and the use of complementary therapies such as coenzyme Q10 and vitamin D supplementation. Novel approaches, including PCSK9 inhibitors and nutraceuticals, have also shown promise in mitigating statin-related muscle adverse effects. In conclusion, statins offer a promising therapeutic avenue for NAFLD management, particularly in patients with elevated cardiovascular risk. This review updated the statins' therapeutic potential in NAFLD, their molecular mechanisms, statin-induced myopathy, extra-hepatic effects, and preventive strategies for future research.